Systematic reviews of the effectiveness of quality improvement strategies and programmes. Issue 4 (1st August 2003) - Grimshaw, J; McAuley, L M; Bero, L A; Grilli, R; Oxman, A D; Ramsay, C; Vale, L; Zwarenstein, M
Abstract : Systematic reviews provide the best evidence on the effectiveness of healthcare interventions including quality improvement strategies. The methods of systematic review of individual patient randomised trials of healthcare interventions are well developed. We discuss methodological and practice issues that need to be considered when undertaking systematic reviews of quality improvement strategies including developing a review protocol, identifying and screening evidence sources, quality assessment and data abstraction, analytical methods, reporting systematic reviews, and appraising systematic reviews. This paper builds on our experiences within the Cochrane Effective Practice and Organisation of Care (EPOC) review group.